2018
DOI: 10.3389/fpls.2018.01739
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2 Improves Photosynthesis Under High Temperature by Attenuating the Functional Limitations to Energy Fluxes, Electron Transport and Redox Homeostasis in Tomato Leaves

Abstract: Elevated atmospheric CO2 improves leaf photosynthesis and plant tolerance to heat stress, however, the underlying mechanisms remain unclear. In this study, we exposed tomato plants to elevated CO2 (800 μmol mol-1) and/or high temperature (42°C for 24 h), and examined a range of photosynthetic and chlorophyll fluorescence parameters as well as cellular redox state to better understand the response of photosystem II (PSII) and PSI to elevated CO2 and heat stress. The results showed that, while the heat stress dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 42 publications
5
52
0
Order By: Relevance
“…In a previous study on tomato, plants exposed to 42 • C for 24 h showed a decline of net photosynthesis, maximum PSII photochemical efficiency and electron transport rate [28]. Consistent with these findings, our results further demonstrated that a short-term (60 min) heat shock at 45 • C was sufficient to cause significant effects on the photochemistry in detached tomato leaves.…”
Section: Discussionsupporting
confidence: 92%
“…In a previous study on tomato, plants exposed to 42 • C for 24 h showed a decline of net photosynthesis, maximum PSII photochemical efficiency and electron transport rate [28]. Consistent with these findings, our results further demonstrated that a short-term (60 min) heat shock at 45 • C was sufficient to cause significant effects on the photochemistry in detached tomato leaves.…”
Section: Discussionsupporting
confidence: 92%
“…Photosynthesis is the sum of a series of complex metabolic reactions. It is the basis for the survival of the biological community and the material and energy basis for the growth and development of plants 26,45 . Photosynthetic capacity plays an important role in plant yield 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…However, elevated temperature reduced the inhibition of Rubisco carboxylation activity by elevated CO 2 (Pérez, Alonso, Zita, Morcuende, & Martínez‐Carrasco, ). Whereas short‐term heat stress reduced photosynthetic parameters in chamber‐grown tomato ( Solanum lycopersicum ), elevated CO 2 mitigated most of these effects (Pan, Ahammed, Li, & Shi, ). At ambient CO 2 , heat waves in field‐grown soybean reduced photosynthesis during both flowering and pod‐filling stages.…”
Section: Effects Of Elevated Temperatures and Interacting Climate Varmentioning
confidence: 99%